Morphometric analysis of rat and mouse musculoskeletal tissues using high field MRI - Olivia L. Dyer; Stephanie G. Cone (Scientific Reports)
Abstract The knee is a complex articulating joint composed of bones and fibrous connective tissues with anatomy retained across species including humans, pigs, dogs, rats, and mice. Imaging developments in high field magnetic resonance imaging (MRI) has enabled non-destructive 3D structural analysis of small animal joints to further these preclinical models. The goal of this work was to apply MRI techniques for rodent knee joints using a high field MRI scanner and to characterize the morphometry of the four primary ligaments and medial and lateral menisci. Briefly, female rat and mouse knees were imaged in a 9.4T MRI scanner and the cross-sectional area (CSA) of the ligaments and the meniscal heights and widths were recorded. Tissue dependent relationships were observed in the rat and mouse ligaments. The PCL was the largest ligament in the rats with a CSA of 0.35 ± 0.08 mm2, while the LCL was the largest ligament in the mice, with a CSA of 0.054 ± 0.017 mm2. Rat and mouse meniscal width had an anatomical location dependent relationship, while meniscal height did not. This will support future work exploring morphometric effects due to aging, injury, and disease in preclinical animal models.